2017
DOI: 10.1371/journal.pone.0181394
|View full text |Cite
|
Sign up to set email alerts
|

Indicators to measure risk of disaster associated with drought: Implications for the health sector

Abstract: IntroductionBrazil has a large semiarid region, which covers part of 9 states, over 20% of the 5565 municipalities in the country and at 22.5 million persons, 12% of the country’s population. This region experiences recurrent and extended droughts and is characterized by low economic development, scarcity of natural resources including water, and difficult agricultural and livestock production. Local governments and communities need easily obtainable tools to aid their decision making process in managing risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 29 publications
2
38
0
3
Order By: Relevance
“…In addition, the Canadian case study proposes the Hazard Vulnerability Similarity Index which uses the local knowledge by comparing similarity between different sites, since learning is of key importance to resilience [29]. Finally, the traditional knowledge, possessed by local communities, should be merged with scientific tools to bring better understanding of local risks and more efficient risk management [90].…”
Section: Indicators Are More Often Used On a Global Space Scale Than mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the Canadian case study proposes the Hazard Vulnerability Similarity Index which uses the local knowledge by comparing similarity between different sites, since learning is of key importance to resilience [29]. Finally, the traditional knowledge, possessed by local communities, should be merged with scientific tools to bring better understanding of local risks and more efficient risk management [90].…”
Section: Indicators Are More Often Used On a Global Space Scale Than mentioning
confidence: 99%
“…The study [90] hopes that its risk index would be useful in addressing some of Sendai's priority areas related to drought and health, [89] that the combination of approaches to assess physical vulnerability to debris flows would contribute to the resilience of mountain areas, and [40] is the only case study implementing Sendai regulative, carrying out the study of climate adaptability in the city of Beijing, China. In addition, the case studies of Ischia island [72], Venice [73] and Saudi Arabia [91], to state some of them.…”
Section: Indicators Are Predominantly Related To Vulnerability and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilian northeast (NE) usually faces periods of severe drought, with the most severe ever recorded occurring between 2012 and 2016 [4]. Besides reducing the reservoirs to critical volumes, which results in water supply deficiency [5], this rainy scarcity favors cyanobacterial blooms [6,7]. A literature survey of publications about cyanobacterias between 1930 and 2016 showed that the highest number of toxic bloom events occurred in Pernambuco (PE) state, where was described the presence of microcystins, cylindrospermopsin, five variants of saxitoxin (STX) and anatoxin-a(S) in freshwater [8].…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian northeast (NE) usually faces periods of severe drought, with the most severe ever recorded occurring between 2012 and 2016 (4). Besides reducing the reservoirs to critical volumes, which results in water supply deficiency (5), this rainy scarcity favors cyanobacterial blooms (6, 7). A literature survey of cyanobacteria publication from 1930 to 2016 showed that the highest number of toxic bloom events occurred in Pernambuco (PE) state, where was described the presence of microcystins, cylindrospermopsin, five variants of saxitoxin (STX) and anatoxin-a(S) in freshwater (8).…”
Section: Introductionmentioning
confidence: 99%